Contemporary Indian Art and the 'Semiotic Eye': Issues and Perspectives. (January 2014) - Khanwalkar, Seema
This article has a focus on the semiotic value of contemporary Indian art practice. It takes a fundamental position that in India, the conceptual response to contemporary art (painting and visual art) needs to be understood for its potential to create ongoing interpretations, and not just for what it aims its potential meaningful destination to be. The article further emphasizes the need to understand these new expressions in terms of Peirce's notion of the 'Interpretant', against the established fact that they are fundamentally distinct from the traditional art practices in their intent and purpose. The impetus for this position comes from the significant shifts, continuities and discontinuities that art in India has seen since 'modernism'. Traditional Indian theories had highly developed treatises elaborating upon the formal processes that led to an experiential 'object' of transformation and ananda (joy). The attempt is to call for analytical frameworks that semiotic theory can provide to the works of Indian artists who have, 'ontologically progressed beyond the initial appeal of Modernism and the attendant desire to use acknowledged Western idioms. More than anything else, they respond to politics, and work to impact social justice. This is where tradition appears-via narrative' (Seid, 2007, p. 13).